LTE communications and networks : femtocells and antenna design challenges - Ur-Rehman, Masood; Safdar, Ghazanfar Ali, 1973- (Wiley, 2018)
A COMPREHENSIVE RESOURCE TO THE LATEST DEVELOPMENTS OF SYSTEM ENHANCEMENT TECHNIQUES OF FEMTOCELLS, POWER MANAGEMENT, INTERFERENCE MITIGATION AND ANTENNA DESIGN LTE Communications and Networks fills a gap in the literature to offer a comprehensive review of the most current developments of LTE Femtocells and antennas and explores their future growth. With contributions from a group of experts that represent the fields of wireless communications and mobile communications, signal processing and antenna design, this text identifies technical challenges and presents recent results related to the development, integration and enhancement of LTE systems in portable devices. The authors examine topics such as application of cognitive radio with efficient sensing mechanisms, interference mitigation and power management schemes for the LTE systems. They also provide a comprehensive account of design challenges and approaches, performance enhancement techniques and effects of user's presence on the LTE antennas. LTE Communications and Networks also highlights the promising technologies of multiband, multimode and reconfigurable antennas for efficient design of portable LTE devices. Designed to be a practical resource, this text: . Explores the interference mitigation, power control and spectrum management in LTE Femtocells and related issues. Contains information on the design challenges, different approaches, performance enhancement and application case scenarios for the LTE antennas. Covers the most recent developments of system enhancement techniques in terms of Femtocells, power management, interference mitigation and antenna design. Includes contributions from leading experts in the field Written for industry professionals and researchers, LTE Communications and Networks is a groundbreaking book that presents a comprehensive treatment of the LTE systems in the context of Femtocells and antenna design and covers the wide range of issues related to the topic.